Ruptured Primary Ovarian Ectopic Pregnancy: A rare case report - Singh, Swapnil; Alwani, Madhuri; Malukani, Kamal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary ovarian pregnancy occurs quite rarely and that too usually in young highly fertile multiparous women. Risk factors include previous pelvic inflammatory disease, IUD use, endometriosis, and assisted reproductive technologies. Its presentation often is difficult to distinguish from that of tubal ectopic pregnancy. We report a case where a young Second gravida with previous LSCS presented with two months amenorrhea along with abdominal pain presented to us and was diagnosed as ectopic pregnancy and was confirmed intra-operatively and histopathologically as primary ovarian pregnancy, managed successfully with laparotomy followed by partial ovariectomy.